2019
DOI: 10.1111/1475-6773.13247
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nursing home reporting of major injury falls for quality measurement on nursing home compare

Abstract: Objective To assess the accuracy of nursing home self‐report of major injury falls on the Minimum Data Set (MDS). Data Sources MDS assessments and Medicare claims, 2011‐2015. Study Design/Methods We linked inpatient claims for major injury falls with MDS assessments. The proportion of claims‐identified falls reported for each fall‐related MDS item was calculated. Using multilevel modeling, we assessed patient and nursing home characteristics that may be predictive of poor reporting. We created a claims‐based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 23 publications
1
49
1
Order By: Relevance
“…A study comparing MDS assessments and Medicare hospital claims between 2011 and 2015 found that falls with major injury were less likely to be documented in the MDS for nonwhite residents than white residents when compared to hospital claims for major injury falls. 31 Our findings have potential implications for incentivizing nursing homes to provide high-quality care. As part of the 2014 Improving Medicare Post-Acute Care Transformation Act, SNFs, inpatient rehabilitation facilities, home health agencies, and long-term care hospitals are required to report common quality measures.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A study comparing MDS assessments and Medicare hospital claims between 2011 and 2015 found that falls with major injury were less likely to be documented in the MDS for nonwhite residents than white residents when compared to hospital claims for major injury falls. 31 Our findings have potential implications for incentivizing nursing homes to provide high-quality care. As part of the 2014 Improving Medicare Post-Acute Care Transformation Act, SNFs, inpatient rehabilitation facilities, home health agencies, and long-term care hospitals are required to report common quality measures.…”
Section: Discussionmentioning
confidence: 84%
“…First, there is evidence that nursing homes under-report the number of falls in the MDS. 31 Second, we were not able to account for facility-level differences in fall incident reporting practice across SNFs (eg, not reporting near-miss falls, nursing staff assisting residents to the floor but without injuries). 31,35 Third, we excluded residents who died during their SNF stay.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, skepticism about the validity of the self-reported pain QMs seemed consistent with the creative strategies many providers employed to improve their pain scores, some of which could be considered gaming. A recent study using Medicare claims found that a substantial percentage of falls resulting in serious injury (42.5%) were not reported on the MDS (Sanghavi et al, 2020). Given that CMS has changed or replaced several QMs over time, it is likely that CMS too has concerns about some of the QMs.…”
Section: Discussionmentioning
confidence: 99%
“…59 For example, only 57.5% of major injury falls were reported on MDS data compared with actual claims data. 60 Nursing homes have an incentive to under-report indicators of poor quality to receive higher quality ratings and to avoid scrutiny from state surveyors, consumers, advocates, journalists, and managed care payers with whom nursing homes are contracted to provide short-stay care.…”
Section: Centers For Medicare and Medicaid Services Quality Measuresmentioning
confidence: 99%